A scoping review of the role of HIV-related stigma and discrimination in noncommunicable disease care - Stockton, Melissa A.; Giger, Kayla; Nyblade, Laura (PLOS ONE, 2018)
Background People living with HIV are increasingly burdened by noncommunicable diseases (NCDs) as a result of the NCD susceptibility that accompanies increased life expectancy and the rising global prevalence of NCDs. Health systems are being strengthened and programs are being developed to address this burden, often building on HIV care strategies and infrastructure or through integrated care models. HIV remains a stigmatized condition and the role of HIV stigma in the provision of NCD care is not well understood. Methods We conducted a scoping literature review of both peer reviewed and grey literature to identify evidence of the role of HIV stigma in the NCD-care continuum (prevention, diagnosis, care seeking, retention in care, and adherence to treatment of NCDs). We searched PsychInfo and Pubmed and conducted additional searches of programmatic reports and conference abstracts. Included studies were published in English within the past decade and examined HIV-related stigma as it relates to NCD-care or to integrated NCD-and HIV-care programs. Results Sixteen articles met the inclusion criteria. Findings suggest: fear of disclosure, internalized shame and embarrassment, and negative past experiences with or negative perceptions of health care providers negatively influence engagement with NCD care; HIV stigma can adversely affect not only people living with HIV in need of NCD care, but all NCD patients; some NCDs are stigmatized in their own right or because of their association with HIV; integrating NCD and HIV care can both reduce stigma for people living with HIV and a present a barrier to access for NCD care. Conclusion Due to the dearth of available research and the variability in initial findings, further research on the role of HIV stigma in the NCD-care continuum for people living with HIV is necessary. Lessons from the field of HIV-stigma research can serve as a guide for these efforts.